METODE GURU BIMBINGAN KONSELING DALAM MEMBENTUK KONSEP DIRI POSITIF SISWA DARI KELUARGA BROKEN HOME DI SMAN 2 SINJAI - Syamsidar Syamsidar; Nur Fahmi (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam)
The purpose of education is to put the basis of intelligence, knowledge, personality, noble character and the skills to live independently and follow further education. From the educational goals that exist, one of the goals is personality including a positive self-concept. The concept of self for children plays a role so that children can adjust to their environment, so they can be accepted by the environment. Another opinion states that the concept of self together with body image, ideal self (the desired self of individuals) and social self (self perceived by individuals based on what is seen by the community). The influence of broken home in the family is very negative for the child's growth and development, especially if the child has entered adolescence where the child is in dire need of figures as well as the love and intact attention of both parents.